Po drugiej stronie bramy - Teleżyńska, Ewa (Zagłada Żydów. Studia i Materiały, 2011)
The article tells the story of three neighboring families domiciled on Łowicka Street in Warsaw during the war – the Palesters, the Proners and the Grundgands. Henryk Palester lived in his own flat throughout the war even though he was of Jewish origin. His wife Maria cooperated with “Żegota” (Council for Aid of Jews) including Irena Sendler. She helped save, among others, her neighbor and friend Maria Proner. Janina Grundgand organized a whole network of flats and helpers. The article features fragments of the accounts and diaries of a few people she saved. The image that emerges is that of an extraordinarily brave, energetic and good woman, who not only helped to obtain papers, provided shelter and organized means of support, but also offered psychical support, self-confidence, feeling of security and hope. In turn, the neighbors, who remember Janina Grundgand (then Kulwieć) from the post-war period, recall her as an unfriendly, arrogant and selfish person and one with which they could not live under the same roof.